IMPLEMENTASI TAX PLANNING PAJAK PENGHASILAN BADAN PT. INDOJAYA MANDIRI - Ifadhoh, Nurul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The tax payers has full responsibility for counting, depositing and reporting by themselves the amount of tax payableand tax liability. This research is meant to analyze maximisation of tax saving. The effort for tax saving is often doneby tax payer which is known as tax planning. Descriptive research is applied by the researcher in order to discuss theimplementation of tax planning at PT Indojaya Mandiri. The taking of companyâs internal data is performed by theresearcher as a support for the validity of this thesis. The implementation of tax planning as management instrumentin income tax saving is carried out in various ways which do not violate the prevailing tax provisions. Theimplementation of tax planning which is performed by the PT Indojaya Mandiri has not maximize yet. Byimplementing tax planning there is a corporate income tax saving as much as Rp 26,627,299. Therefore, a companywill be avoided from tax waste and will be able to fulfill their tax liability when they implement proper tax planning.Keywords: Tax Planning, Tax Saving, Income Tax.